Permasalahan Sosial Dalam Novel Negeri Di Ujung Tanduk Karya Tere Liye: Tinjauan Sosiologi Sastra Dan Implementasinya Dalam Pembelajaran Sastra Di SMA - Khayati, Arief Nur (2016)
This researchaimed at describing (1)thestructure that build thenovel,(2) social problems contained in the novel Negeri Di Ujung Tanduk, (3) the implementation of the novel structureand the social problemsin the novel into the literary learning in Senior High School. Kind of this research was a qualitative research which focused more on the understanding of meaning, closely reated to certain values. The data used were sentences and paragraphs which showed the structure of thenovel and the social problems contained in the novel Negeri Di Ujung Tanduk. The source of data in this research was the novel Negeri Di Ujung Tanduk written by Tere Liye. The approach used was the literary sociology. The technique of data collection used the technique of observing and taking a note. The data validity used was the technique of triangulation theory. The technique of data analysis used the qualitative method. The results of thisresearch were: (1) Biography of the writer (TereLiye): a writer who always present writings with background of social life and is able to attract many people through her writings. (2) Structurally, the theme of the novel was the political and legal life. Plot in the novel Negeri Di Ujung Tanduk was a mixture. The actors in the novel consisted of the main actor named Thomas and supernumerary actors such asMaryam, Opa Chan, Chai Ten, Lee, uncleLiem, Meggie, Kadek, James, Shinpei, Kris, teacher Alim, JD, Inspector Liu, Rudy andPutri Laila. The setting of time showed morning, noon, afternoon, and night. The setting of place happened most in Macau City, besides, there were several cities such as Jakarta, Hongkong, Singapura, andDenpasar. (3) the social problemsin thenovelNegeri Di Ujung Tanduk: there were fivesocial problems; (a) poverty, (b)crime, (c)family disorganization, (d) war, and(e) breaking the norms. (4) The results of theresearch could be implemented into the literary learning in Senior High School with the teaching material was the results of the research about the novel structureand the teaching material from the results of the research about thesocial problems.